The quality of chest compressions performed by the staff employed in selected units cooperating with the state emergency medical services system - Grzybkowska, Barbara; Sadaj-Owczarek, Kamila (Jakość uciśnięć klatki piersiowej przez osoby zatrudnione w wybranych jednostkach współpracujących z państwowym systemem ratownictwa medycznego, 2023)
The purpose of our research was to compare the quality of chest compressions performed by firefighters, lifeguards, and police officers and to identify any weak points they may have so as to prevent them in the future. Participants of the research were asked to compress the chest of a training phantom for four minutes, and the results were measured separately after the first two and consecutive two minutes. Based on the results, lifeguards have the biggest problem with maintaining the correct depth of compressions, firefighters with upholding the adequate rate, and police officers strainafter two minutes, which influences the quality of chest compressions. The conclusion of the research is that all these groups should receive more obligatory practical training, so that people, who may sooner or later be confronted with a situation in which they have to sustain blood circulation between vital organs, can do it as flawlessly as possible.
Zeszyty Naukowe Collegium Witelona, nr 49(4)/2023, s. 61-69
Keywords: compressions; emergency medical services system; qualified first aid; cardiopulmonary resuscitation; uciski; system ratownictwa medycznego; kwalifikowana pierwsza pomoc; resuscytacja krążeniowo-oddechowa